The effect of multicarbohydrase-phytase complex supplementation on the egg production performance, egg quality, and economics of laying hens - Jayson J. Juan; Ernesto A. Martin; Claro N. Mingala; Paul Wigley; Heather E. Allison; Nicola J. Williams; Joice V. San Andres (Cogent Food & Agriculture)
This study was conducted to assess the effects of the supplementation of a multicarbohydrase-phytase complex (MCP) which contains xylanase, glucanase, arabinofuranosidase, and superdose phytase, and a combination of a xylanase-glucanase and a phytase (XGP) products in a corn-soybean diet with reduced apparent metabolizable energy (AME), digestible amino acids (DAA), and minerals (calcium and phosphorus) on egg production performance, egg quality, and economics of laying hens. Dekalb White layers (n = 480, BW = 1.56 ± 0.03 kg, 42 weeks old) with a mean hen-day egg production rate of 91.43 ± 1.31% were assigned to four diets with 15 replicates of eight layers per group: standard layer diet (SLD), low-density diet 1-(LD1, SLD less 65 kcal/kg AME, 2% DAA, 0.20% Ca, and 0.15% P) + MCP (0.01%), low-density diet 2-(LD2, SLD less 85 kcal/kg AME, 4% DAA, 0.20% Ca, and P) + MCP (0.01%), and LD2 + XGP (0.01% XG and 0.015% P). Diets supplemented with MCP and XGP had comparable production and egg quality to SLD. The LD1 + MCP, LD2 + MCP, and LD2 + XGP had a poor feed conversion ratio (FCR) and a higher mean daily feed intake (FI) than SLD. Eggshells were thicker for LD1 + MCP and LD2 + MCP than SLD and LD2 + XGP from 58 to 61 weeks of age. The income over feed cost (IOFC) was similar among layers fed the test diets. The findings indicated that enzyme supplementation compensated satisfactorily for the reduced amount of DAA and minerals in the diet. Reduction of 65–85 kcal/kg AME caused an adverse effect on FCR and FI of layers.